The movement of natural persons : a CARICOM strategy for trade in services and international trade negotiations : final report - Ifill, Lynette A. R. ([Caribbean Regional Negotiating Machinery] [Christ Church]BB, 2001)
Examines the various negotiations in which CARICOM is engaged viz. the WTO GATS 2000 negotiations, the implementation of Protocol II to the Treaty of Chaguaramas, regional bilateral agreements, the FTAA process, and the Cotonou Agreement. Makes recommendations on the strategy that CARICOM should adopt.